2023
DOI: 10.1530/joe-22-0155
|View full text |Cite
|
Sign up to set email alerts
|

Role of hepatic peroxisome proliferator-activated receptor γ in non-alcoholic fatty liver disease

Abstract: Peroxisome proliferator-activated receptor γ (PPARγ) belongs to a family of nuclear receptors that could serve as lipid sensors. PPARγ is the target of a group of insulin sensitizers called thiazolidinediones (TZD) which regulate the expression of genes involved in glucose and lipid metabolism, as well as adipokines that regulate metabolic function in other tissues. Non-alcoholic fatty liver disease (NAFLD) has a high prevalence worldwide and is even higher in patients with obesity and insulin resistance. TZD-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 127 publications
0
10
0
Order By: Relevance
“…The novel Lipodystrophy 2 cluster included multiple variants related to adipocyte and hepatocyte function. For instance, the cluster included variants near PNPLA3 9 and PPARG 10 , which regulate fatty acid metabolism in both adipocytes and hepatocytes, and epigenomic analysis demonstrated that the Lipodystrophy 2 cluster was enriched in adipocytes ( Fig. 3B ).…”
Section: Discussionmentioning
confidence: 99%
“…The novel Lipodystrophy 2 cluster included multiple variants related to adipocyte and hepatocyte function. For instance, the cluster included variants near PNPLA3 9 and PPARG 10 , which regulate fatty acid metabolism in both adipocytes and hepatocytes, and epigenomic analysis demonstrated that the Lipodystrophy 2 cluster was enriched in adipocytes ( Fig. 3B ).…”
Section: Discussionmentioning
confidence: 99%
“…6 A and D). This is probably because in previous human studies, pioglitazone reduced FAs influx into the liver by enhancing lipid anabolism in adipose tissues 42 , 43 . We found no benefit of pioglitazone to OOC viability and albumin production under Condition A (Fig.…”
Section: Resultsmentioning
confidence: 86%
“…The top-weighted traits included increased hepatic enzymes (aspartate aminotransferase [AST], alanine aminotransferase [ALT], γ-glutamyl transferase [GGT]), increased Homeostatic Model Assessment for Insulin Resistance (HOMA-IR), and decreased insulin sensitivity index. The top-weighted loci included PNPLA3 and PPARG , which regulate the accumulation of fatty acids in the liver and adipose tissue 9,10 . Compared to our prior work, the previous single Lipodystrophy cluster appeared to split into two clusters (Extended Data Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The novel Lipodystrophy 2 cluster included multiple variants related to adipocyte and hepatocyte function. For instance, the cluster included variants near PNPLA3 9 and PPARG 10 , which regulate fatty acid metabolism in both adipocytes and hepatocytes, and epigenomic analysis demonstrated that the Lipodystrophy 2 cluster was enriched in adipocytes (Fig. 3B).…”
Section: Discussionmentioning
confidence: 99%